The Satisfaction of The Students’ Parents Towards Educational Administration of Ban Nongtaobuengrue-yai School, Khoksi Sub-district, Muang District, Khonkaen Province. Under Supervision of Khonkaen Primary Educational Service Area 1. - เกษจ้อย, สิทธิพร; ทะสา, พระวรชัด; ไร่สงวน, พระมหาสัจจารักษ์; ทะสา, พระวรชัด; ชิชะกุล, ประชัน (Journal of Educational Review Faculty of Education in MCU, 2018)
This study was survey research. It was aimed to study: 1) the personal factors of the students’ parents of Ban Nongtaobuengrue-yai school, Khoksi sub-district, Muang district, Khonkaen province, under supervision of Khonkaen primary educational service area 1, 2) the parents’ satisfaction towards educational administration of Ban Nongtaobuengrue-yai school, and 3) the problems and suggestions to develop educational administration of Ban Nongtaobuengrue-yai school. It was found that there were 95 respondents.Majority percent (52.60) were female, and 47.40 percent were male. Most of the respondents (29.50 percent) were age between 41-45 years old, and 96.80 percent were not graduated bachelor degree. Most of the respondents (87.40 percent) were married, most of them (69.50 percent) were the farmers, and earned lower than 10,000 bath a month (72.28 percent). For the overall of the parents’ satisfaction towards educational administration of Ban Nongtaobuengrue-yai school, it was at high mean level ( =3.64)